Photocatalytic Decarboxylative Cyclization of 1,6-Enynes and N-Methacryloyl-2-phenylbenzimidazoles by Potassium Iodide/ Triphenylphosphine Catalysis - Zhang, Jian; Li, Jiao-Zhe; Wang, Ling-Tao; Yu, Xuan-Chi; Zhang, Jun-Hao; Ge, Guo-Ping; Liu, Hongxin; Wei, Wen-Ting (Synlett, 2022)
We describe a photocatalytic decarboxylative cyclization of 1,6-enynes or N-methacryloyl-2-phenylbenzimidazoles for efficient and ecofriendly syntheses of lactams or benzimidazo[2,1-a]isoquinoline-6(5H)-ones, respectively, by the use of KI/PPh3 as a redox catalyst system. In this method, N-hydroxyphthalimide esters were used as alkyl-radical precursors to achieve this decarboxylative cyclization without any dyes, transition-metal catalysts, oxidants, or bases.
Keywords: green chemistry; photocatalysis; transition-metal free; cyclization; lactams; benzimidazoquinolinones